Cultural Aspects of Social Services - Dustmurod Abdinazarovich, Rakhmonov; Akhmat Asamiddinovich, Beknazarov; Makhliyokhon Kushalievna, Normuratova (International Journal of Psychosocial Rehabilitation, 2020)
The article deals with the formation and development of the social service system and the growing need and demand for social services in a pandemic. It also analyzes the content of various factors influencing the development of social services, highlighting its important features in ensuring a meaningful life for people as a social institution. Issues such as the nature, types, forms, and methods of social services as a system; the structure of social service institutions; regional and departmental social services; and the provision of social services are studied on the basis of sources. The authors also point out that social service is divided into general levels and categories, based on an analysis of sources on the conditions and culture of social services. In addition, the article emphasizes the need to develop theoretical models that reflect the professional quality of social services and put forward conclusions and recommendations.